Arabidopsis ROOT HAIR DEFECTIVE3 is involved in nitrogen starvation‐induced anthocyanin accumulation. Issue 8 (2nd February 2015) - Wang, Jing; Wang, Yan; Yang, Ju; Ma, Chunli; Zhang, Ying; Ge, Ting; Qi, Zhi; Kang, Yan
Abstract Anthocyanin accumulation is a common phenomenon seen in plants under environmental stress. In this study, we identified a new allele of ROOT HAIR DEFECTIVE3 (RHD3) showing an anthocyanin overaccumulation phenotype under nitrogen starvation conditions. It is known that ethylene negatively regulates light‐ and sucrose‐induced anthocyanin biosynthesis. We hypothesized that RHD3 achieves its negative effect on anthocyanin biosynthesis via an ethylene‐regulating pathway. In support of this, similar to rhd3 mutants, the Arabidopsis ethylene signaling mutants etr1, ein2, and ein3/eil1 showed an anthocyanin overaccumulation phenotype under nitrogen starvation conditions. The ethylene precursor ACC strongly suppressed anthocyanin accumulation, dependent on ETR1, EIN2, EIN3/EIL1, and, partially, RHD3. In addition, inactivating RHD3 partially reversed the suppressive effect of ETO1 inactivation‐evoked endogenous ethylene production on anthocyanin accumulation. The expression of nitrogen starvation‐induced anthocyanin biosynthesis genes was negatively regulated by RHD3, but ethylene response genes were positively regulated by RHD3. Wild‐type seedlings overexpressing RHD3 showed similar phenotypes to rhd3 mutants, indicating the existence of a fine‐tuned relationship between gene expression and function. RHD3 was initially identified as a gene involved in root hair development. This study uncovered a new physiological function of RHD3 in nitrogen starvation‐induced anthocyanin accumulation and ethylene homeostasis. [Correction added on 6 August 2015, after first online publication: "RND3" corrected to "RHD3".]